Analisis Akuntabilitas Dan Transparansi Pengelolaan Dana Desa - Paskah Ika Nugroho; Yumna Oktaviana (Fakultas Manajemen Pemerintahan, Institut Pemerintahan Dalam Negeri, 2025)
ABSTRACT This study aimed to analyze the implementation of the principles of Accountability and Transparency in Village Fund Management in Plumbon Village, Suruh District, Semarang Regency. Minister of Home Affairs Regulation Number 20 of 2018 is used as an indicator to assess the practice of implementing the principles of Accountability and Transparency by paying attention to several stages such as Planning, Implementing, Administrating, Reporting, and Carrying out Accountability. This study is a case study that used a qualitative approach. The method used was a descriptive qualitative method to provde an accurate and systematic description based on the data that had been collected before. The data collection techniques included interviews with related parties, practical observations and documents, as well as supporting documentations. The overall final result of this study showed that Plumbon Village Government’s quite good while implementing the principles of accountability and transparency in managing its village funds. However, for the principle of accountability at implementing and administrating stages, some indicator were not appropriate. Moreover, the principle of transparency for the reporting and carrying out accountability stages was appropriate but can be improved for a better village governance ahead. Keywords: Accountability, Transparency, Village Fund Allocation. ABSTRAK Penelitian ini bertujuan untuk menganalisis penerapan prinsip Akuntabilitas dan Transparansi dalam Pengelolaan Dana Desa di Desa Plumbon, Kecamatan Suruh, Kabupaten Semarang. Permendagri Nomor 20 Tahun 2018 digunakan sebagai indikator untuk menilai praktik penerapan prinsip Akuntabilitas dan Transparansi dengan memperhatikan beberapa tahapan seperti Perencanaan, Pelaksanaan, Penatausahaan, Pelaporan, dan Pertanggungjawaban. Penelitian ini merupakan studi kasus yang menggunakan pendekatan kualitatif. Metode yang digunakan adalah kualitatif deskriptif untuk memberikan deskripsi yang akurat dan sistematis berdasarkan data yang telah dikumpulkan. Teknik pengumpulan data berupa wawancara dengan pihak terkait, observasi praktik dan dokumen, serta dokumentasi sebagai pendukung. Hasil dari penelitian secara keseluruhan Pemerintah Desa Plumbon sudah cukup baik untuk penerapan prinsip akuntabilitas dan transparansi dalam pengelolaan dana desa. Namun untuk prinsip akuntabilitas pada tahap pelaksanaan dan penatausahaan terdapat indikator yang belum sesuai. Dan pada prinsip transparansi untuk tahapan pelaporan dan pertanggungjawaban sudah sesuai namun dapat ditingkatkan untuk pemerintahan desa yang lebih baik. Kata Kunci : Akuntabilitas, Transparansi, Alokasi Dana Desa.